2022
DOI: 10.3390/nu14122455
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D in Different Trimester with Hemoglobin during Pregnancy

Abstract: The association between vitamin D and hemoglobin has been suggested. Vitamin D can affect erythropoiesis by the induction of erythroid progenitor cell proliferation and enhance iron absorption by regulating the iron-hepcidin-ferroportin axis in monocytes. However, this relationship in pregnant women is scarce. The purpose of this study was to investigate the association between plasma vitamin D levels with hemoglobin concentration in pregnant women considering each trimester and iron supplementation. The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…One explanation for the discrepancy between these findings and the current study is that characteristics specific to the population group under study (such as pregnant women, children, or older individuals), may impact the significance of the relationship. For example, one study even found variations in the association between vitamin D deficiency and anemia according to pregnancy trimester [ 66 ]. Interestingly, that study also found that the positive association between vitamin D and Hb was only significant in pregnant women who were taking iron supplements, potentially due to the role of vitamin D on the absorption of available iron, through hepcidin.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the discrepancy between these findings and the current study is that characteristics specific to the population group under study (such as pregnant women, children, or older individuals), may impact the significance of the relationship. For example, one study even found variations in the association between vitamin D deficiency and anemia according to pregnancy trimester [ 66 ]. Interestingly, that study also found that the positive association between vitamin D and Hb was only significant in pregnant women who were taking iron supplements, potentially due to the role of vitamin D on the absorption of available iron, through hepcidin.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple observational studies report the association between vitamin D deficiency, high hepcidin levels and anemia in conditions characterized by inflammatory processes such as inflammatory bowel disease, acute infectious disease, severe traumatic injury and healthy preterm infants [127][128][129][130], while in other cases, vitamin D and iron deficiencies did not correlate with high hepcidin levels, even in the presence of inflammation [131]. Furthermore, in a study of pregnant women, vitamin D supplementation had no effect on hepcidin, ferritin and inflammatory status [106], however, the adequate intake of vitamin D during pregnancy correlated with better hemoglobin levels [132]. High-dose vitamin D supplementation improved iron status but did not affect hepcidin levels in athletes [107] nor in patients affected by chronic kidney disease [108].…”
Section: Nutritional Modulation Of Hepcidinmentioning
confidence: 97%
“…However, the role of vitamin D in anemia prevention and iron absorption remains controversial [22]. In animal-and population-based pregnancy studies, Qiu et al [23] and Si et al [24] both reported a positive association between blood vitamin D levels and iron status. A cross-sectional study conducted by Mayasari et al revealed an association between dietary intake and serum hepcidin levels during pregnancy [25].…”
Section: Introductionmentioning
confidence: 99%